The Effect of General and Partner-Specific Alliance Experience on Joint R&D Project Performance - Hoang, Ha; Rothaermel, Frank T. (Academy of Management Journal, 2005)
Drawing on the organizational learning literature, we posited that both general, diverse-partner experience and partner-specific experience contribute to alliance performance, but at a declining rate. We tested hypotheses in unique data on the objective performance of projects between large pharmaceutical firms and biotechnology partners. The general alliance experience of the biotechnology partners, but not of the pharmaceutical firms, positively affected joint project performance. This relationship exhibited diminishing marginal returns. Contrary to predictions, partner-specific experience had a negative, marginally significant effect on joint project performance.